Actinobacteria Associated With Arbuscular Mycorrhizal Funneliformis mosseae Spores, Taxonomic Characterization and Their Beneficial Traits to Plants: Evidence Obtained From Mung Bean (Vigna radiata) and Thai Jasmine Rice (Oryza sativa) - Lasudee, Krisana; Tokuyama, Shinji; Lumyong, Saisamorn; Pathom-aree, Wasu (Frontiers in microbiology, 2018)
In this study, we report on the isolation of actinobacteria obtained from spores of and provide evidence for their potential in agricultural uses as plant growth promoters and . Actinobacteria were isolated from spores of using the dilution plate technique and media designed for the selective isolation of members of specific actinobacterial taxa. Six strains namely 48, S1, S3, S4, S4-1 and SP, were isolated and identified based on16S rRNA gene sequences. Phylogenetic analysis showed that isolate SP belonged to the genus with KLBMP 1282 as its closest neighbor. The remaining isolates belonged to the genus . Two isolates, 48 and S3 were most closely related to DSM 44293 . Isolates S4 and S4-1 shared the highest 16S RNA gene similarity with NBRC 127772 . Isolate S1 showed its closest relationship with the type strain of NBRC14228 . The ability of these isolates to produce indole-3-acetic acid (IAA), siderophores and the ability to solubilize phosphate were examined. All isolates produced siderophores, four isolates produced IAA and two isolates solubilized inorganic phosphate at varying levels. isolate S3 showed the highest IAA production with high activities of phosphate solubilization and siderophore production. The inoculation of mung beans ( ) with this strain resulted in a significant increase in fresh weight, root length and total length as an effect of IAA production. In an experiment with rice ( ), isolate S3 promoted the growth of rice plants grown in low nutritional soil under induced drought stress. This report supports the view that the inoculation of rice with plant growth promoting actinobacteria mitigates some adverse effects of low nutrient and drought stress on rice.